Rate-splitting multiple access in satellite-terrestrial communication systems: performance analysis - Huu Q. Tran; Khuong Ho-Van (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
This paper investigates the throughput and outage probability (OP) of rate splitting multiple access (RSMA) in satellite–terrestrial communication networks. By dividing user messages into common and private parts, RSMA enhances spectral efficiency and user fairness while addressing hardware impairments and co-channel interference. The proposed hybrid system model is analyzed and compared with non-orthogonal multiple access (NOMA) under various power allocation coefficients and channel conditions. Results show that RSMA achieves lower OP and higher throughput than NOMA, particularly in dense multi-cell deployments. Numerical evaluations further demonstrate RSMA’s robustness against interference and hardware limitations, underscoring its potential as a reliable solution for next-generation satellite–terrestrial relay networks.